Mold burden in house dust and its relationship with asthma control - Segura-Medina, Patricia; Vargas, Mario H.; Aguilar-Romero, José Manuel; Arreola-Ramírez, José Luis; Miguel-Reyes, José Luis; Salas-Hernández, Jorge (Respiratory medicine, 2019)
Some evidences indicate that exposure to molds or their products can be relevant for the loss of asthma control. Thus, we measured the mold burden present inside houses of subjects with asthma, and evaluated its relationship with asthma control. Markers of asthma control in adult patients residing in Mexico City were evaluated through questionnaires and spirometry. Dust was collected from the patients’ houses and its fungal content was determined by mold specific quantitative PCR (MSQPCR) for 36 fungal species. Forty-two patients with asthma (12 males, 30 females) with a mean age of 45 years (18–76 years) were included in the study. The level of asthma control measured through the Asthma Control Test ranged from 9 to 25 (mean 20.9). The FEV1/FVC ratio fluctuated from 38 to 106 %predicted (mean, 87.4 %predicted). Associations between mold burden and asthma control differed between males and females. Thus, concentrations of some molds, particularly Aspergillus fumigatus, Aureobasidium pullulans, Stachybotrys chartarum, Alternaria alternata, Cladosporium cladosporioides 2, Cladosporium herbarum, and Epicoccum nigrum, were negatively associated with parameters of asthma control in male subjects, but not in female patients. Our results showed that potential indoor exposure to some molds is associated with less asthma control in male subjects. •qPCR for 36 mold species were done in dust from houses of 42 patients with asthma.•Content of some mold species correlated with loss of asthma control.•The negative impact of molds on asthma control was observed in males but not in females.